Multimodal Multidisciplinary Management of Patients with Moderate to Severe Pain in Knee Osteoarthritis - Veronese, Nicola (2022)
Funding Information: Open access funding provided by Università degli Studi di Palermo within the Nicola Veronese reports personal fees from IBSA, Mylan, and Fidia outside of the submitted work. Cyrus Cooper reports personal fees from Alliance for Better Bone Health, Amgen, Eli Lilly, GSK, Medtronic, Merck, Novartis, Pfizer, Roche, Servier, Takeda, and UCB outside of the submitted work. Jean-Yves Reginster reports CRUI-CARE Agreement. Funding Information:grants from IBSA-Genevrier, Mylan, CNIEL, and Radius Health (through his institution); consulting fees from IBSA-Genevrier, Mylan, CNIEL, Radius Health, and Pierre Fabre; fees for participation in review activities from IBSA-Genevrier, Mylan, CNIEL, Radius Health, and Teva; and payment for lectures from Ag-Novos, CERIN, CNIEL, Dairy Research Council (DRC), Echolight, IBSA-Genevrier, Mylan, Pfizer Consumer Health, Teva, and Theramex outside of the submitted work. Olivier Bruyère reports grants or lecture fees from Amgen, Aptissen, Biophytis, IBSA, MEDA, Mylan, Novartis, Sanofi, Servier, SMB, TRB Chemedica, UCB, and Viatris outside of the submitted work. Ali Mobasheri declares personal fees from Abbott, Abbvie, Achē Laboratórios Farmacêuticos, Galapagos, GSK Consumer Healthcare, Kolon TissueGene, Laboratoires Expansciences, Merck, Pacira Biosciences, Pfizer, Sanofi, and Servier. François Rannou reports grants or lecture fees from Pierre Fabre, Mylan, MSD, Thuasne, IBSA, Pfizer, Genévrier, Expanscience, Scarcell, Skindermic, and Peptinov. Ida K. Haugen reports grants from Pfizer and is a consultant for Novartis outside of the submitted work. Elaine M. Dennison declares grants/fees from Pfizer, Lilly, UCB, and Viatris. Philip G. Conaghan is supported in part by the National Institute for Health and Care Research (NIHR) Leeds Biomedical Research Centre (the views expressed are those of the authors and not necessarily those of the NHS, the NIHR, or the Department of Health), and reports consultancies or lecture fees from AbbVie, Amgen, AstraZeneca, Eli Lilly, Galapagos, GSK, Grunenthal, Pfizer, Novartis, and UCB. Nasser M. Al-Daaghri, Antonella Fioravanti, Sara Cheleschi, Jean-Pierre Pelletier, Maarten de Wit, Etienne Cavalier, Radmila Matijevic, Germain Honvo, Régis Pierre Radermecker, René Rizzoli, Jaime Branco, Andrea Laslop, María Concepción Prieto Yerro, Alberto Migliore, Gabriel Herrero-Beaumont, and Nicholas R. Fuggle declare that they have no conflicts of interest. Publisher Copyright: © 2022, The Author(s).